2017
DOI: 10.1080/07420528.2017.1397684
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase II trial of induction chemotherapy followed by cisplatin chronotherapy versus constant rate delivery combined with radiotherapy

Abstract: Chronotherapy is no longer a novel concept in cancer treatment after approximately 20 years of development. Many clinical trials have provided strong supporting evidence that chronomodulated treatment yields better results than a traditional dosage regimen. This study aimed to evaluate the adverse reactions, effect on immune functions, and therapeutic efficacy of chronomodulated infusion versus flat intermittent infusion of cisplatin (DDP) combined with intensity-modulated radiation therapy (IMRT) in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…These resistance mechanisms emerge from processes that are controlled by the circadian clock (Sancar et al, 2010;Dallmann et al, 2014;Dallmann et al, 2016). Thus far, clinical studies have shown that several adverse effects experienced by cancer patients taking cisplatin-based chemotherapy decreases when cisplatin is applied in a chrono-modulated context (Li et al, 2015;Zhang et al, 2017). The results and outcomes of these studies indicate that the proper timing of drug administration reduces cisplatin-induced adverse effects in patients.…”
Section: Drug Resistance Emerges Out Of Cell Mechanisms Under Circadimentioning
confidence: 99%
“…These resistance mechanisms emerge from processes that are controlled by the circadian clock (Sancar et al, 2010;Dallmann et al, 2014;Dallmann et al, 2016). Thus far, clinical studies have shown that several adverse effects experienced by cancer patients taking cisplatin-based chemotherapy decreases when cisplatin is applied in a chrono-modulated context (Li et al, 2015;Zhang et al, 2017). The results and outcomes of these studies indicate that the proper timing of drug administration reduces cisplatin-induced adverse effects in patients.…”
Section: Drug Resistance Emerges Out Of Cell Mechanisms Under Circadimentioning
confidence: 99%
“…[247][248][249] Recent studies in the field of cancer chronotherapy have examined chronomodulated variable rate infusions of docetaxel, cisplatin, or 5-FU with or without radiotherapy for the treatment of advanced nasopharyngeal carcinoma. [250][251][252][253][254][255] Chronomodulated variable rate infusions of chemotherapeutics resulted in less adverse effects [250][251][252][253]255 and improved cellular immune numbers in virtually all clinical trials. [250][251][252]254,255 Few studies have examined the effects of chronomodulated oral chemotherapy treatment.…”
Section: Cancer Treatments Chemotherapymentioning
confidence: 99%
“…[250][251][252][253][254][255] Chronomodulated variable rate infusions of chemotherapeutics resulted in less adverse effects [250][251][252][253]255 and improved cellular immune numbers in virtually all clinical trials. [250][251][252]254,255 Few studies have examined the effects of chronomodulated oral chemotherapy treatment. [256][257][258] One such retrospective study compared the effects of morning with evening dosing of 6-mercaptopurine and methotrexate for the treatment of childhood acute lymphoblastic leukemia in 118 children and reported that evening dosing increased disease-free survival and reduced the risk of relapse by 2.5 times.…”
Section: Cancer Treatments Chemotherapymentioning
confidence: 99%
“…However, despite decades of intense research of circadian rhythm in cancer, chronotherapy has had limited impact on the mainstream clinical oncology 75 . This might be explained by its failure to show significant improvement in overall survival in previous large clinical trials [76][77][78] . However, at the same time, positive effects of nocturnal chemotherapy on toxicity and tolerability have been demonstrated for almost all types of chemotherapeutic drugs, including: 5-fluorouracil, irinotecan, doxorubicin and most platinum-based drugs [79][80][81][82] .…”
Section: Cancer Treatment During Sleepmentioning
confidence: 99%